Hepatoprotective effect of crude polysaccharides extracted from Ganoderma lucidum against carbon tetrachloride-induced liver injury in mice - Susilo, Raden Joko Kuncoroningrat (Vet World, 2019)
BACKGROUND AND AIM: Natural products are currently widely used as alternative treatments for liver disease. The study aimed to determine the hepatoprotective effect of crude polysaccharides extracted from Ganoderma lucidum against liver injury induced by carbon tetrachloride (CCl(4)). MATERIALS AND METHODS: Twenty-four male BALB/C mice were randomly divided into six groups. Serum and liver samples were taken on day 10 after G. lucidum administration. The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA), superoxide dismutase (SOD), and catalase (CAT) were measured using enzyme-linked immunosorbent assays, and the histology of the liver was evaluated using light microscopy. RESULTS: G. lucidum extract significantly decreased the levels of ALT, AST, and MDA and significantly increased the levels of SOD and CAT. In the histological evaluation, the liver tissue of CCl(4)-treated mice exhibited hydropic degeneration, necrosis, and sinusoidal dilatation. G. lucidum extract administration improved this liver tissue histopathology. CONCLUSION: Crude polysaccharides extracted from G. lucidum showed a hepatoprotective effect, regenerating damaged liver tissue.